Ohio Range Subglacial rock core cosmogenic nuclide data ... - Mukhopadhyay, Sujoy (U.S. Antarctic Program (USAP) Data Center, 2020)
The data set consists of cosmogenic berrylium-10 and aluminum-26, along with neon-21, in a set of 4 rock-cores obtained from the Ohio Range, West Antarctica. The rock cores were obtained using the WInkie drill. The depth to the cores varies from 12 meters to 28 meters. The recovered rock cores analyzed for the cosmogenic isotopes varies from 22 cm long to 50 cm long. The data include the following formation: sample details, cosmogenic berrylium-10, aluminum-26 and upper bounds for cosmogenic 21 (since samples have nucleogenic 21) and the step heating data for neon. The data are in Mircrosoft excel format. ...